Cell signaling in sperm midpiece ensures quiescence and survival in cauda epididymis. Issue 5 (5th October 2021) - Devi, Archana; Kushwaha, Bhavana; Maikhuri, Jagdamba P; Singh, Rajender; Gupta, Gopal
Abstract : Sperm in most mammalian species including rat, mice and human are kept completely quiescent (motionless) and viable for up to a few weeks in the cauda epididymis before ejaculation. Vigorous motility is initiated almost instantly upon sperm release from cauda during ejaculation. The molecular mechanisms that suppress sperm motility but increase cell survival during storage in cauda epididymis are not known. Intracellular signaling via phosphorylation cascades is quick events that may regulate motility and survival of transcriptionally inactive sperm. Pathscan intracellular signaling array provided the preliminary picture of cell signaling in quiescent and motile rat sperm, indicating upregulation of cell-survival pathways in quiescent sperm, which were downregulated during motility activation. Interactome of signaling proteins involved in motility activation was constructed by Search Tool for the Retrieval of Interacting Genes (STRING) software, which identified mitogen activated protein kinase-p38 (MAPK-p38), AKT, mTOR and their downstream target p70S6K as the key kinases regulating sperm function. Further validation was achieved by western blotting and pathway activators/inhibitors. Immunofluorescence localized the kinase proteins in the sperm mid-piece region (mitochondria), a known extra-nuclear target for these signaling pathways. Activators of these kinases inhibited sperm motility but increased viability, and vice versa was true for inhibitors, in most of the cases. Activators and inhibitors also affected sperm mitochondrial membrane potential, ATP content and reactive oxygen species (ROS) levels. Data suggest that sperm motility and survival are inversely complementary and critically regulated by intracellular cell signaling. Aberrant cell signaling in caudal sperm may affect cell survival (sperm concentration) and motility of ejaculated sperm.